Sentiment Analysis of the Relocation of the National Capital on Social Media X - Dewi, Yesi Ratna; Saraswati, Ni Wayan Sumartini; Monny, Maria Osmunda Eawea; Sarasvananda, Ida Bagus Gede; Andika, I Gede (Politeknik Ganesha Medan, 2025)
The relocation of the national capital is a national strategic development project that seeks input from the public. This research analyzes public sentiment towards the relocation of the capital city using the Lexicon SVM method with data from X social media. The analysis was conducted in two languages, namely Indonesian and English, to find out how public opinion on the relocation of Indonesia's capital city at the global level. The sentiment classification results show that in Indonesian, public sentiment tends to be balanced with a model accuracy of 86.79%, where 51.3% is positive sentiment and 48.7% is negative. Meanwhile, in English, positive sentiment is more dominant with a model accuracy of 89.64%, where 83.3% is positive sentiment and 16.7% is negative sentiment. Evaluation using confusion matrix shows that this model provides good results, with high precision, recall, and F1-score values. Visualization using WordCloud and frequency analysis of unigrams, bigrams, and trigrams showed that positive sentiments mostly discussed the development aspects and government policies, while negative sentiments highlighted the social and economic impacts of the relocation. In addition, further analysis shows that public sentiment fluctuates based on important government announcements and major events related to the project. These findings demonstrate the importance of monitoring public opinion over time to understand shifts in perception. This research provides insights to the government and policymakers in understanding public opinion regarding the relocation of the nation's capital. By understanding sentiment patterns, more appropriate policies can be designed to increase public acceptance of the project and address public concerns effectively.